Discharge Characteristics of a Trapezoidal Labyrinth Side Weir with One and Two Cycles in Subcritical Flow - Emiroglu, M. Emin; Aydin, M. Cihan; Kaya, Nihat (Asce-Amer Soc Civil Engineers, 2014)
A labyrinth weir provides an effective way to increase weir crest length without an associated increase in structure width. Labyrinth side weirs have important advantages compared to conventional side weirs in term of discharge capacity, length of the channel opening, and nappe height over the weir. A different equation is needed for each number of cycles to determine the discharge coefficient of labyrinth side weir. Unlike labyrinth spillways, one or two cycles are mostly sufficient for the labyrinth side weirs to accommodate the required discharge. This study examines the hydraulic characteristics of trapezoidal labyrinth side weirs with two cycles in a subcritical situation and the effect on discharge capacity of using single or multiple cycles in side weirs with the same length openings and crest lengths. The results show that a side weir with one cycle has slightly greater discharge coefficient. In addition, the variation of the discharge capacity was investigated for both one-cycle and two-cycle side weirs with the same opening length in the main channel. The results show that the relationship obtained for a one-cycle side weir is not suitable for multiple-cycle side weirs if dimensionless weir length L/B = 0.5. Consequently, the relationships for the De Marchi coefficient of discharge in a subcritical flow for trapezoidal labyrinth side weirs were introduced as functions of dimensionless variables. The empirically obtained equations for discharge coefficient agree considerably with the experimental data. (C) 2014 American Society of Civil Engineers.
Keywords: Side weir; Water discharge; Discharge coefficient; Intake; Labyrinth weir; Open-channel flow